High dynamic range images: Evolution, applications and suggested processes - Rafi, Ahmad; Tinauli, Musstanser; Izani, Mohd (2007)
Three dimensional (3D) and Computer Graphics (CG) industries nowadays require 'instant' realism and extreme special effects while imposing the balance in cost, time and solution acceptance standard. It has been known that realistic rendering is time consuming, difficult to use, complex, expensive and often produces insufficient digital output to predict particularly in the earl), visualization process. This paper focuses on one of the emerging technologies, High Dynamic Range Image (HDRI) and how it can be developed in achieving effective solution, while maintaining 'realism' or required result based on a specific application. We firstly introduce the overall HDRI processes before continue to present a framework of captured Low Density, Range Image (LDRI) source sequence effectively in HDRI environment. This paper concludes with discussions and lists the application of HDRI.